Integration of gender for better science: Supporting scientists in research - Wright, Iain A. (International Livestock Research Institute, 2016)
The CGIAR Livestock and Fish Program supports scientists to think about gender. It teams up technical scientists with gender researchers. Working together they can come up with ideas on how to work on gender in research programmes. This approach has been quite successful. It also needs to be translated to in-field research practices. In the past, researchers were doing household surveys, but it was difficult to tease out gender information from the data because it was not disaggregated. The researchers understood that there is a need to design surveys differently and ask questions of men and women to understand their perspectives. This was rarely done in the past. The teaming up of researchers makes it possible to get a better understanding of perspectives of the different genders. Interview with Iain Wright (ILRI) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568